Volar Locking Plate Fixation for Distal Radius Fractures by Intraoperative Computed Tomographic–Guided Navigation - Akira Kawabata, MD; Yusuke Sogabe, MD; Yukiko Morimoto, MD; Kiyohito Takamatsu, MD, PhD (Journal of Hand Surgery Global Online, 2020)
Purpose: Unstable distal radius intra-articular fractures require restoration of alignment. Exact fixation of intra-articular fragments is ideal. Here, we employed intraoperative computed tomography (CT) navigation to insert screws accurately in the intra-articular dorsal fragments during treatment with a volar locking plate for distal radius intra-articular fractures. The main purposes of this study were to evaluate the accuracy of this procedure and the postoperative stability of the articular fragments through CT findings, as well as to assess clinical outcomes. Methods: This study included 26 patients with distal radius fractures, who were treated with a volar locking plate using intraoperative CT navigation with a minimum follow-up of 12 months. Mean patient age was 63 years and mean follow-up was 16 months. We examined the position of the inserted distal screws and articular displacement on preoperative, intraoperative, and post–bone union CT images. The 3 distal ulnar screw positions that influence the stability of the dorsoulnar articular fragment were evaluated. The Mayo wrist score and Disabilities of the Arm, Shoulder, and Hand score were also clinically evaluated. Results: Computed tomography evaluation revealed that the distal locking screws were appropriately inserted at the subchondral position, with sufficient length to stabilize the dorsal fragments, and reduction and stability of the articular fragment were acceptable. At the final follow-up, mean Mayo wrist score was 90.8 and mean Disabilities of the Arm, Shoulder, and Hand score was 9.6. Conclusions: Intraoperative CT navigation was successfully used for volar locking plate fixation of intra-articular distal radius fractures. Computed tomography evaluation revealed that the screws were precisely inserted for articular fragments and bone union was achieved, maintaining good intra-articular alignment. The findings demonstrate the accuracy of volar locking plate fixation assisted by intraoperative CT navigation and the good clinical outcomes of this procedure. Type of study/level of evidence: Therapeutic IV.